Literatur Review: Penerapan Metode Analytic Hierarchy Process Sebagai Teknik Prioritas Kebutuhan Perangkat Lunak - Izzati, Afifah Nurul (INTEK : Jurnal Informatika dan Teknologi Informasi, 2023)
AHP is one of the popular techniques used in prioritizing software requirements. This study aims to determine the application of AHP as a software requirements priority technique by reviewing thirty literature related to the application of AHP as a software requirements prioritization technique pub-lished in 2017 to 2023. The results of the study explain that the application of AHP has several ad-vantages, but on the other hand AHP also has some drawbacks. Over time, a number of literatures have discussed the development of AHP which aims to minimize weaknesses in the application of AHP. The development of AHP is by integrating AHP with Planning Game, MoSCoW, QFD, and Fuzzy. In addition, development is also carried out by adding new algorithms, namely ReDCCahp and Enhanced AHP. The results of this study provide a useful reference for researchers and practitioners in the field of requirements engineering in prioritizing software requirements using AHP.